1994
DOI: 10.1007/bf00040696
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a novel, nuclear-encoded, NAD+-dependent glyceraldehyde-3-phosphate dehydrogenase in plastids of the gymnosperm Pinus sylvestris L.

Abstract: Angiosperms and algae possess two distinct glyceraldehyde-3-phosphate dehydrogenase (GAPDH) enzymes, an NAD(+)-dependent tetramer involved in cytosolic glycolysis and an NADP(+)-dependent enzyme of the Calvin cycle in chloroplasts. We have found that the gymnosperm Pinus sylvestris possesses, in addition to these, a nuclear-encoded, plastid-specific, NAD(+)-dependent GAPDH, designated GapCp, which has not previously been described from any plant. Several independent full-size cDNAs for this enzyme were isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…Previous work indicated that genes for eukaryotic GAPDH enzymes are descendants of an ancient gene family which existed in the common ancestor of extant eubacteria (4,19,26). This view is supported by the GAPDH gene phylogeny in Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Previous work indicated that genes for eukaryotic GAPDH enzymes are descendants of an ancient gene family which existed in the common ancestor of extant eubacteria (4,19,26). This view is supported by the GAPDH gene phylogeny in Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Chloroplastic GAPDH uses preferentially NADPH and can be activated either by reduction or by metabolites (for a recent paper on the subject, see Baalmann et al, 1995). The situation with chloroplastic GAPDH is very complex, since the protein can use either NADH or NADPH as a substrate, both activities being present in the chloroplast, as evidenced recently in Pinus sylvestris (Meyer-Grauen et al, 1994). The NADPH-dependent enzyme is up-regulated by the thioredoxin system and is a tetramer composed of either the 4A subunits or 2A and 2B subunits.…”
Section: {D) Cf^-atpasementioning
confidence: 99%
“…In vitro transcription, translation and import pTK39 was linearized with SacI, purified, transcribed in the presence of 1 mM 7mG(5')ppp(5')G (New England Biolabs) with T7 RNA polymerase (Pharmacia) and translated as described [27]. Preparation of intact chloroplasts from 80 g of 14-day old pea leaves and import were performed according to Clausmeyer et al [6] with a protocol kindly provided by R.-B.…”
Section: Enzyme Assaymentioning
confidence: 99%